Anteseden Kinerja Anggaran Dengan Komitmen Organisasi Dan Kepemimpinan Sebagai Pemoderasi : Studi Pada Kementerian Agraria Dan Tata Ruang/Badan Pertanahan Nasional - Medaniarty, Reni; Harnovinsah; Darmansyah (CV ODIS, 2024)
The purpose of this study was to analyze and prove empirically the effect of variables on leadership size, budget planning, competence, motivation, and regulation on budget performance. The research was conducted at the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency using a qualitative approach by collecting primary data through a 5-score Likert scale questionnaire. Technical sample selection using convenience sampling with 80 respondents The data analysis method in this study uses a structural equation model (SEM) approach using partial least squares (PLS). The results of the study show that budget planning and regulatory factors have a significant positive effect on budget performance, while organizational commitment has not been proven to be able to significantly strengthen the effect of budget planning on budget performance. However, organizational commitment has been proven to be able to strengthen the effect of regulation on budget performance. Leadership is not proven to strengthen the influence of budget planning on budget performance insignificantly, but leadership strengthens the moderation between regulations on budget performance significantly